Improving Information Access Through Information Technology-Based Extension for Farmers in Tadang Palie Village, Ulaweng District, Bone Regency: Peningkatan Akses Informasi Melalui Penyuluhan Berbasis Teknologi Informasi untuk Petani di Desa Tadang Palie Kecamatan Ulaweng Kabupaten Bone - Andi Sepalawan (Jurnal Ilmiah Sosio Agribis, 2026)
Information technology (IT) serves as a communication medium for agricultural extension workers to access information and demonstrate it in the field. This study aimed to analyze the utilization of IT by extension workers and the improvement of IT-based extension services in enhancing farmers' access to agricultural information. The research was conducted in Tadang Palie Village, Ulaweng District, Bone Regency, from August 2025 to February 2026. A quantitative descriptive method with a Likert scale approach was used. The population consisted of 15 farmer groups with a total of 375 farmers (25 farmers per group). A random sample of 30 farmers (2 per group) was selected. The assessment categories were: high (66.68–100%), moderate (33.34–66.67%), and low (0–33.33%). The results showed that Whatsapp was the most frequently used platform (97.78%), followed by YouTube (86.67%), TikTok (76.67%), and Facebook (73.33%). Meanwhile, Instagram usage was low (35.55%). The average improvement in IT-based extension services for accessing agricultural information reached 96.44% (high category). This indicates that IT utilization enhances extension activities in delivering agricultural information, both directly and through social media. Extension serves as non-formal education providing guidance, mentoring, problem-solving, and training, enabling farmers to expand their knowledge and develop their farming practices.